2006
DOI: 10.4314/ajbr.v8i3.35746
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of aqueous extract of raw <i>Aloe Vera</i> leaves: histopathological and biochemical studies in rat and tilapia

Abstract: Forty-five juvenile tilapia and 30 weanling albino rats exposed to water containing 50, 100 and 150ppm of aqueous extract of Aloe vera leaves for 96 hours and 28 days, respectively were used for this study. Fifteen tilapia and 10 rats exposed to clean water (0 ppm A. vera) served as controls. Clinical signs, mortality, gross and histologic organ pathology in the tilapia; weekly haematology, plasma biochemical parameters and organ pathology were monitored in the rats. Fish cultured in water containing A. vera e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
10
0
2
Order By: Relevance
“…For example, Taiwo et al (2005) reported that aqueous extract of raw A. vera leaves at concentration as high as 50 ppm caused tissue necrosis, gill, heart, liver, and kidney damage in tilapia and also caused severe normocytic normochromic anemia and increased plasma AST levels in rats. Similarly, our previous study reported that 4 % Aloe/kg diet resulted in hypochromic microcytic anemic GIFT-tilapia juveniles with poor defense mechanisms against physiological stress.…”
Section: Discussionmentioning
confidence: 98%
“…For example, Taiwo et al (2005) reported that aqueous extract of raw A. vera leaves at concentration as high as 50 ppm caused tissue necrosis, gill, heart, liver, and kidney damage in tilapia and also caused severe normocytic normochromic anemia and increased plasma AST levels in rats. Similarly, our previous study reported that 4 % Aloe/kg diet resulted in hypochromic microcytic anemic GIFT-tilapia juveniles with poor defense mechanisms against physiological stress.…”
Section: Discussionmentioning
confidence: 98%
“…Taiwo et al [37]; and Jegede [38] reported histopathological effects of A. vera on tilapia species. To the best of our knowledge there is no report to date on the effects of A. vera on growth performance, haemalogical and biochemical parameters of tilapia species, GIFT-Oreochromis niloticus in particular, except a recent study by Dotta et al [39].…”
Section: Introductionmentioning
confidence: 99%
“…Estudos sobre o efeito de plantas em tilápias nilóticas já foram realizados por outros autores. Taiwo et al (2005) testaram o efeito do extrato aquoso das folhas de Aloe vera L. em vários órgãos do peixe, inclusive as brânquias, e concluíram que essa planta possui substâncias tóxicas potentes para esses animais. Entre as alterações observadas nas brânquias, os pesquisadores destacaram a degeneração vacuolar dos filamentos e necrose das células epiteliais e a infiltração heterofílica da submucosa branquial.…”
Section: Discussionunclassified